PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP UNIVERSITY PERFORMANCE DENGAN LEARNING ORGANIZATION DAN UNIVERSITY CULTURE SEBAGAI VARIABEL INTERVENING - Octavia Lianna (Business Accounting Review, 2015)
This study aimed to examine the affect of transformational leadership on university performance with learning organization and university culture as the intervening variables. The samples and data used in this study were obtained from 420 students in 6 private universities in Surabaya by using questionnaire. The sample selection was done by purposive sampling. This hypothesis was tested by using Partial Least Square (PLS) and descriptive analysis by using SPSS. The results showed transformational leadership did not directly influence on university performance. Transformational leadership had significant and positive influence on learning organization and university culture. Learning organization and university culture had significant and positive influence on university performance.